Penggunaan Grafik Gerak Untuk Meningkatkan Daya Tarik Siaran Radio Visual - Utomo, Budi; Ismed, Mohammad; Satyahadi, Alfred (P3M Politeknik Negeri Media Kreatif, 2025)
Visual radio is a form of radio media that has visual elements so that what previously we could only hear, can now be watched. This transformation is attributed to the integration of visual elements into radio broadcast programs. This research is motivated by the need to explore how one of the visual elements in broadcasts, namely motion graphics, can be implemented in radio broadcast production. The problem addressed is how motion graphics can be effectively applied in radio programs and their impact on media quality. The study aims to understand the implementation process and its effects on the quality of radio programs using a qualitative descriptive approach with in-depth interviews and observations, this research is expected to illustrate the application of motion graphics in radio broadcasting. The findings are anticipated to provide solutions for enhancing radio program quality, offering significant advertising opportunities with visually engaging content.